Model Toleransi dalam Eksegese Khotbah Areopagus - Mba, Deni Alfian (Religió: Jurnal Studi Agama-agama, 2016)
This article is a literature research on tolerance model through the exegesis of Areopagus sermon. Having known the exact model of tolerance, someone will be able to tolerate correctly. Given one source of intolerance is a misinterpretation of the teachings of the scriptures, this article invites the reader to examine the tolerance source from the interpretation of the Bible. This article focuses on two things: (1) the doctrine of a model of tolerance; and (2) the techniques of interpretation of Scripture in the Catholic religion exegetical analysis. For this purpose, the authors chose Areopagus sermon text mentioned in the book of Acts chapter 17 verse 22 to verse 34. By explaining the exegesis of those verses, this article aims to find a model precise tolerances. The text itself tells about the story of Paul’s sermon, a preacher of the early Christianity, brought before the Court Areopagus in Athens Greece. Based on the analysis of exegesis is known that the model of tolerance shown in this story is a model of tolerance active. Paul could communicate well with his audience coming from different social and cultural background. Apparently, he succeeded to deliver his ideas and teaching accurately by utilizing a good knowledge about the social and cultural situation of Athens. [Artikel ini merupakan penelitian literatur pada model toleransi melalui penafsiran dari khotbah Areopagus. Setelah diketahui model toleransi yang tepat, seseorang akan mampu bertoleransi dengan cara yang benar. Mengingat salah satu sumber intoleransi adalah salah tafsir ajaran kitab suci, artikel ini mengajak pembaca untuk meneliti sumber toleransi dari penafsiran Alkitab. Artikel ini berfokus pada dua hal: (1) doktrin model toleransi; dan (2) teknik penafsiran kitab suci dalam tradisi Katolik, yakni analisis eksegese. Untuk tujuan ini, penulis memilih teks khotbah Areopagus yang terdapat dalam Kitab Kisah Para Rasul Pasal 17 ayat 22 sampai ayat 34. Dengan menjelaskan penafsiran ayat-ayat, artikel ini bertujuan untuk menemukan model toleransi yang tepat. Teks itu sendiri menceritakan tentang kisah khotbah Paulus, seorang pengkhotbah dari Kekristenan awal, yang dibawa ke Mahkamah Areopagus di Athena Yunani. Berdasarkan analisis eksegese diketahui bahwa model toleransi yang ditunjukkan dalam cerita ini adalah model toleransi aktif. Paulus bisa berkomunikasi dengan baik dengan para pendengarnya yang berasal dari latar belakang sosial dan budaya yang berbeda. Rupanya, ia berhasil menyampaikan ide-ide dan ajarannya secara akurat dengan memanfaatkan pengetahuan yang baik tentang situasi sosial dan budaya dari Athena